Pengendalian Persediaan dengan Memperhatikan Pemesanan Gabungan dan Permintaan Berdistribusi Poisson di Toko X - Anthonia Lubalu; I Gede Agus Widyadana (Jurnal Titra, 2022)
This study uses the Monte Carlo simulation method by generating random numbers according to the data distribution test. This research was conducted in seven stages, the first is observation and problem identification to ascertain what are the obstacles in Store X. The second stage is literature study to become a theoretical basis that can be used in solving existing problems. the third stage is data collection, this stage is carried out by conducting interviews and asking for sales data from Store X. The next stage is data processing, the fifth stage is data validation, this stage is carried out to ensure the distribution of the data that has been obtained. The sixth stage is ordering simulation and the last stage is drawing conclusions and suggestions. The results obtained from the simulation show that the costs incurred by the Store when placing an order per product are Rp 230,713,967 while the costs incurred by Store when using a combined order is Rp 211,976,977. Based on these data, it is known that Store can save costs of Rp 18,736,896 when placing a combined order.